Comparison between thoracic low-dose computed tomography and conventional-dose computed tomography in evaluating anemia: A preliminary study in a Chinese screening cohort - Zhang, Jianing; Wu, Minghao; Huang, Jinchao; Li, Shixia; Ye, Zhaoxiang (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To investigate and evaluate the value of thoracic low dose computed tomography (LDCT) scan in the diagnosis of anemia. Materials and Methods: 661 patients who received thoracic computed tomography (CT) examination and underwent a peripheral blood examination were retrospectively included. 341 patients underwent conventional dose CT (CDCT), and 320 patients underwent LDCT. Regions of interest (ROI) were placed on the left ventricular cavity (LV), descending aorta (DAo), and interventricular septum (IVS). The corresponding CT attenuation was measured, and the CT attenuation difference between LV and IVS (IVS-LV) and between DAo and IVS (IVS-DAo) was calculated, respectively. One-way analysis of variance (ANOVA) and linear regression were performed to analyze the relation between these indicators and Hb levels. Receiver operating characteristic (ROC) curve was used to evaluate prediction performance. Results: Both attenuation on LDCT and CDCT showed significant differences between the healthy group and the anemic group (P < 0.05). In the LDCT group, the LV and DAo were more relevant with the hemoglobin (Hb) level (correlation coefficient 0.618 and 0.602) than other indicators, with AUCs of 0.815 (95% CI: 0.763–0.868) and 0.803 (95% CI: 0.747–0.859), respectively. The linear regression formulas for Hb level with the LV and DAo were 19.14 + 0.15 × HU (95% CI: [16.52, 21.75] + [0.12, 0.17] × HU) and 19.46 + 0.16 × HU (95% CI: [16.55, 22.36] + [0.13, 0.18] × HU), respectively. Youden’s index indicated that 37.5 HU and 38.5 HU were the best thresholds to diagnose anemia for LV and DAo, respectively. In the CDCT group, the LV and IVS-LV got obviously higher correlation coefficients (0.813 and 0.812), with AUCs of 0.831 (95% CI: 0.786–0.877) and 0.851 (95% CI: 0.808–0.894), respectively. The optimal thresholds for LV and IVS-LV were 40.5 HU and 9.5 HU, respectively. Conclusions: In LDCT examinations, an approximation of Hb level and detecting of anemia can be conducted based on simple attenuation measurements.